Narrowing gaps between research and policy development in climate change adaptation work in the water resources and agriculture sectors of Cambodia - Va Dany (2018)
© 2015 The Author(s). Published by Taylor & Francis. Narrowing research and policy, while challenging, is especially important in climate change adaptation work (CCA) due to the high uncertainties involved in planning for climate change. This article aims to seek stakeholders’ opinions regarding how research and policy development can be bridged within the Cambodian water resources and agriculture sectors. The study used institutional ethnography methods with informants from government organizations, local academia, and development partners (DPs). This article identifies a number of challenges, and barriers for narrowing research–policy development gaps, including: limited effectiveness of governmental policies and planning; lack of relevant information required to promote evidence-based planning and policy development; and communication barriers. Evidence-based planning is valued by government officials most when there is actual and effective implementation of policies and plans. In practice, this often implies that governmental policies and plans need be scoped and scaled down to meet the available budget, and thus be achievable. In the long term, it also means building the capacity for policy-relevant research on climate change adaptation within Cambodia. Engaging policy stakeholders in research process for co-producing adaptation knowledge, and introducing knowledge intermediaries are suggested by informants as means to narrowing gaps between research and policy development. The presence of the Cambodia's Prime Minister in research–policy dialogues is recommended as important for attracting the attention of high-level policy makers. Policy relevance As a least developed and highly climate-vulnerable country, Cambodia has received climate change funding to implement a number of climate adaptation initiatives. Cambodia is likely to receive more climate change finance in the future. This article aims to assist evidence-based planning, in particular, through policy-relevant research on CCA, so that resources for adaptation in Cambodia are used effectively and efficiently. This research also directly benefits the sustainable development of the country.